0345 Pesticide exposure during re-entry tasks and harvesting in vineyards: results of the pestexpo program. (23rd June 2014) - Baldi, Isabelle; Lebailly, Pierre; Bouvier, Ghislaine; Rondeau, Virginie; Bouchart, Valérie; Canal-Raffin, Mireille; Garrigou, Alain
Abstract : Objectives: Physical contact with treated crops, animals or other surfaces is responsible for the transfer of pesticides to the worker's skin in agricultural tasks and makes their cutaneous absorption possible. In the Bordeaux area (France), the PESTEXPO study described levels of pesticide exposure and identified their determinants during re-entry and harvesting in vineyards. Method: Between 2002 and 2007, 46 days of work involving re-entry tasks and 48 harvesting days were observed to analyse exposures to dithiocarbamates or folpet. The potential determinants were generated from the following parameters collected on standardised forms during field observations: i)general conditions of the task, ii)operator characteristics, iii)estate characteristics, iv) task conditions and v)characteristics of the last treatment involving folpet or dithiocarbamates, including delay since treatment. Dermal contamination was assessed using patches placed on the skin and hand-washing at the end of each working phase. Results: Daily median contamination was 1 967.7 μl of mixture during re-entry (90e percentile: 5 045.3 μl) and 18.7 μl during harvesting (90e percentile: 911.4 μl). Contamination level was strongly correlated to the type of task. For re-entry, the highest contaminations were observed during raising of wires and cutting of branches. During the harvest, the contamination was maximal for grape-picking. The delay since the last treatment and the rate of active ingredient per hectare played a role, together with meteorological factors, crop and farm characteristics, gloves and clothes. Conclusions: Our results underline the necessity to take into account exposures during re-entry and harvest when considering pesticide exposure, both for epidemiological research and preventive action.